Impacts of Changes in Forest and Economic Policy and Business Preconditions in Russia and Finland - (:unkn) unknown (Finnish Forest Research Institute, 2011)
This report investigates what have been the changes in Russian forest and economic policy as well as in business preconditions during past years, how these changes have effected the Russian forest sectorand what kinds of effects these changes might have on the Finnish forest sector.The first chapter of the report takes a look at the different steering measures in Russian forest policy and discusses how they have affected forestry in practice and have the policy objectives been reached. We compare the Finnish and the Russian forest management guidelines and discuss the differences in silvicultural practices of the countries. The second chapter studies the impact of Russian roundwood and sawnwood exports on markets from a Finnish perspective. The third chapter presents the results of a study on the quality of imported sawlogs and grade distributions of sawnwood. The fourth chapter discusses the Russian residential networks, what kind of options Russia offers for Finnish timber construction enterprises and what is the economic and employment impact potential in Finland and Northwest Russia.
Keywords: Venäjä; kilpailu; metsäpolitiikka; puurakentaminen; raakapuun vienti; sahatavaran vienti; yhteistyöverkosto; customs duties; economic impact; export; forest policy; import; international trade; investments; joint interest companies; networks; residential construction; roundwood; Russia; sawnwood; stumpage prices; wood quality